Diversidade espacial e temporal de mosquitos (diptera: culicidae) e a sua importância médica em áreas verdes urbanas e residenciais associadas em Fortaleza - May, Guillermo Jesus Guillermo (2018)
INTRODUCTION: Mosquitoes (Diptera: Culicidae) have relevance in public health, as a taxonomic group that gathers a number of species that participate as vectors in the natural cycles of many arboviroses. In Ceará there have been recorded 161 species of mosquitoes from which 24 have records in the municipality of Fortaleza. The risk for the emergency of new aboviruses in Brazil is related to the existence of large cities and their interaction with areas that have the ideal conditions to maintain the arboviral cycles. Given the heterogeneity of space and time, of these natural and artificial environments, it is necessary identify high density foci, based in spatial and temporal geo-referenced data. OBJECTIVES: To analyze the spatial and temporal distribution of the mosquito species in urban green areas and the associated premises, as well as their relationship with arboviral diseases in both dry and rainy season in Fortaleza. METHODS: A longitudinal study of the physical and ecological characteristics related to the presence of mosquito species was performed trough field collection, taxonomic identification and temporal and spatial analysis. RESULTS: A total of 1799 mosquitoes were collected, sorted in 11 taxa an 10 species from 7 different genera were identified. The majority (72%; n=1297) were Culex mosquitoes followed by Mansonia sp. (12%; n=220). Less than 3% of the collected mosquitoes were Aedes aegypti (n=16) and Ae. Albopictus (n=26). Other public health important mosquitoes like Anopheles sp., Ochlerotatus scapularis, Oc. taeniorhynchus, and Mansonia sp. were found. Also there was no previous published reports for the locality of Fortaleza and the State of Ceará for two of the collected species (Coquillettidia nigricans and Uranotaenia sp). The beginning of the rainy season registered the highest abundance and diversity of all the survey stages in all study areas and the majority of species were found both in the domiciliary and green areas. It was found evidence of the variation in the mosquito species distribution according with the interaction characteristics from each area.